Strategi Guru Baca Tulis Qur’an dalam Mengatasi Kesulitan Membaca Al-Qur’an pada Siswa Kelas VIII di MTs Al Fatimiyah Karawang - Wihelis Fitriani; Abu Bakar Umar; Ilham Fahmi (Universitas Muhammadiyah Enrekang, 2021)
The difficulty of reading the Qur'an is an obstacle to learning activities in the classroom, this is the background for the author to examine these problems. Then, this study aims to determine the difficulties experienced by students in reading the Qur'an, then the supporting and inhibiting faktors for teachers in overcoming them, then the strategies used by the Reading and Writing Al-Qur'an teachers in overcoming difficulties in reading the Qur'an. The method used in this study is a qualitative research method, this type of research is descriptive and the research approach uses a phenomology approach. Then the subjects in this study were students of class VIII MTs Al Fatimiyah Karawang and the research sample amounted to 20 non-mukim students. The instrument used is data collection techniques by means of interviews, observation and documentation. The results of this study indicate that the strategies used by the teacher can overcome students' difficulties in reading the Qur'an including introducing hijaiyah letters first, holding private and creating more interesting learning. Based on data collection obtained in the field, it is known that the strategy carried out is able to improve learning outcomes to read the Qur'an Keywords: Strategy, difficulty reading the Al-Qur’an, Al-Qur’an hadith The difficulty of reading the Qur'an is an obstacle to learning activities in the classroom, this is the background for the author to examine these problems. Then, this study aims to determine the difficulties experienced by students in reading the Qur'an, then the supporting and inhibiting faktors for teachers in overcoming them, then the strategies used by the Reading and Writing Al-Qur'an teachers in overcoming difficulties in reading the Qur'an. The method used in this study is a qualitative research method, this type of research is descriptive and the research approach uses a phenomology approach. Then the subjects in this study were students of class VIII MTs Al Fatimiyah Karawang and the research sample amounted to 20 non-mukim students. The instrument used is data collection techniques by means of interviews, observation and documentation. The results of this study indicate that the strategies used by the teacher can overcome students' difficulties in reading the Qur'an including introducing hijaiyah letters first, holding private and creating more interesting learning. Based on data collection obtained in the field, it is known that the strategy carried out is able to improve learning outcomes to read the Qur'anKeywords: Strategy, difficulty reading the Al-Qur’an, Al-Qur’an hadith